Sustainment and adaptation of systems navigation and psychosocial counseling across HIV testing clinics in Vietnam: A qualitative assessment - Sophia M. Bartels; Minh X. Nguyen; Trang T. Nguyen; Adams L. Sibley; Hong Linh T. Dang; Ha T. T. Nong; Ngan T. K. Nguyen; Ha V. Tran; Teerada Sripaipan; Byron J. Powell; Clare Barrington; Luz M. Reyes; et al. (Implementation Research and Practice)
Background Few evidence-based interventions have been successfully scaled up and sustained long-term. Within an implementation trial testing strategies for scale-up of the Systems Navigation and Psychosocial Counseling (SNaP) intervention for people who inject drugs (PWID) with HIV across HIV testing clinics in Vietnam, we sought to assess if the implementation of SNaP was sustained after study support ended and to identify factors, including adaptations, that affected SNaP sustainment. Method Across all 42 SNaP clinics, we surveyed clinic staff at 6–10 months post-study completion to assess SNaP sustainment. We purposively selected six high and six low-sustaining clinics and conducted 31 in-depth interviews with clinic staff ( n  = 23) and clinic directors ( n  = 8). Interviews were coded and analyzed using thematic analysis informed by the Integrated Sustainability Framework. Matrices were used to compare themes across high and low-sustaining clinics. Results 1/12 clinics sustained all of SNaP's core components, 2/12 would continue to sustain SNaP if they had new PWID patients, and the remainder did not fully sustain SNaP but continued conducting a modified version, including shorter or fewer SNaP sessions, tailoring SNaP to participants’ specific needs, and conducting SNaP-style counseling for all clients. Facilitators of sustainment included leadership directives to clinic staff around SNaP sustainment, clinicians’ belief in SNaP's effectiveness, and SNaP's perceived fit with clinic activities and mission. Major barriers to SNaP sustainment included lack of funding for PWID outreach activities, time, staff, training continuity, and systemic challenges with getting PWID into care, such as poverty and lack of transportation. Conclusions We identified the challenge of sustaining the SNaP intervention long-term, the ubiquity of intervention adaptations, and multi-level barriers and facilitators to intervention sustainment. These findings demonstrate the need for sustainment strategies and could inform trials of strategies to improve the longevity of effective HIV interventions for populations that are disproportionately affected by this epidemic.